Relação entre energia metabolizável e aminoácidos sulfurosos para frangas leves - Pinheiro, Sara Gomes (2015)
The aim of this study was to determine the optimal relationship between the level of recommendation of metabolizable energy (ME) and digestible methionine + cystine (M+C dig.) for pullets and laying hens. The experimental design was completely randomized factorial distributed in 4 levels of digestible methionine+cystine (M+C dig.) x 3 levels metabolizable energy (ME). The diets had two recommendation bases for M+C dig.; one for 100% of the recommendation, and one which can meet the proposed varied ± 10% of this recommendation. For ME were suggested three levels, one being the recommendation of literature and other varying ± 5% to 12 treatments. From 1 to 6 weeks there was a significant extent on the interaction of the factors analyzed in all tested variables, showing that dietary changes both in M+C as the energy density can result in better development of gastrointestinal tract, increasing the efficiency of absorption of feed, and consequently improving feed conversion. In 7 to 12 weeks, there was only significant difference for bursa weight, serological tests, small intestine histomorphometric and the variables that the nitrogen balance. No hepatic steatosis occurred at any phases. It is recommended to use 0.667% M+C dig. associated with 2755 kcal / kg of EM (ratio MS: M + of 4130.32 digestible C) in the diet for pullets (1 to 6 weeks), which corresponds to a daily intake of 184 mg M+C dig/pullet. For 7-12 weeks, the recommendation was 0.497% of M+C dig. associated to 2,755 kcal/kg of EM (ME:M+C of 5543.26), which corresponds to a daily intake of 136 mg of M+C/pullet. In the laying period (24 to 44 weeks) was observed interaction the factors tested for the performance variables and quality of the eggs except for egg weight, egg mass, specific gravity, shell thickness, yolk weight, percentage of albumen and yolk. In the slaughter of variables was no interaction abdominal fat weight and liver, but had no severe hepatic steatosis degree. In serological tests and small intestine and uterus histomorphometric was no interaction, and adjust the regression for all variables analyzed, showing that different levels of M+C dig. associated with different energy levels can positively change the serological activity and cell proliferation, increases 26 nutrient absorption and promotes greater gland activity in the uterus of this shell. In laying (45 to 65 weeks) was no interaction of the evaluated factors for all performance variables except for egg weight. There was a quadratic regression for all groups tested, except for feed intake. And in the egg quality variables, the shell weights and yolk and yolk percentage were the only ones that do no interference, and there was significant response to regression for yolk weight and yolk and albumen percentages. For the slaughter of variables there was no interaction to live and liver weight, and not significant response to factor regression. All serological tests showed interaction and factorial regression was not only significant adjustment to the quadratic model for aspartate aminotransferase and albumin. In the variables linked to nitrogen balance was no interaction and significant effect to factor regression for all analyzes. And for small intestine and uterus histomorphometry, and liver had no significant effect on the responses found. Therefore, we recommend the use of 0.704% M+C dig. (corresponded to a daily intake of 676 mg M+C dig./layer). Associated with a level of 2900 kcal/kg ME (ratio ME:M+C of 4119.32) in the diet of laying hens between 24 and 44 weeks of age. And for laying hens, between 45 and 65 weeks of age, we recommend the use of 0.685% M+C dig., corresponding a consumption of 781 mg of M + C dig. /layer/day, associated with a level of 2940 kcal/kg ME (ratio ME:M + C dig. of 4291.97).